Nicotine ameliorates schizophrenia-like cognitive deficits induced by maternal LPS exposure: a study in rats - Uta Waterhouse; Vic E. Roper; Katharine A. Brennan; Bart A. Ellenbroek (Disease Models & Mechanisms, 2016)
Maternal exposure to infectious agents is a predisposing factor for schizophrenia with associated cognitive deficits in offspring. A high incidence of smoking in these individuals in adulthood might be, at least in part, due to the cognitive-enhancing effects of nicotine. Here, we have used prenatal exposure to maternal lipopolysaccharide (LPS, bacterial endotoxin) at different time points as a model for cognitive deficits in schizophrenia to determine whether nicotine reverses any associated impairments. Pregnant rats were treated subcutaneously with LPS (0.5 mg/kg) at one of three neurodevelopmental time periods [gestation days (GD) 10-11, 15-16, 18-19]. Cognitive assessment in male offspring commenced in early adulthood [postnatal day (PND) 60] and included: prepulse inhibition (PPI), latent inhibition (LI) and delayed non-matching to sample (DNMTS). Following PND 100, daily nicotine injections (0.6 mg/kg, subcutaneously) were administered, and animals were re-tested in the same tasks (PND 110). Only maternal LPS exposure early during fetal neurodevelopment (GD 10-11) resulted in deficits in all tests compared to animals that had been prenatally exposed to saline at the same gestational time point. Repeated nicotine treatment led to global (PPI) and selective (LI) improvements in performance. Early but not later prenatal LPS exposure induced consistent deficits in cognitive tests with relevance for schizophrenia. Nicotine reversed the LPS-induced deficits in selective attention (LI) and induced a global enhancement of sensorimotor gating (PPI).